The relationship Between strong attention and moving reaction sport the player of joust - Abbas, Basam (Journal of Physical Education, 2019)
First Chapter 1. introduction & significance of the research The upper mental operations will affect on level of the psychological preparation For the players such as Attention , perception , mental development and fist reaction and others , they are very important elements in the fields of scientific research for the competition sport . whereas the focus or attention and perception have significant roles in the principles of performance t develop the level of the players of sport specially the sport of joust because this is attacking game and defending game in same time, therefore it needs high ability and sever energy and faster movements with strong lading and high focusing the attention has changed faster because the situation has changeable continuously and the player most change his movements with high attentions , but this movements may become so tardy (slowly) . From this point of view the significance of the research came clear to recommend to focus on the training and developing the ability tolerance for the mental operations not for the competition only but for developing the skills 2. The problem of the research Basically on what had came in the introduction and the significance of the research to focus on the develop the skills an t preparing new programs of training the players of joust and t use several styles training in the attacking or defense. 3. Research's Goals - to make known the relationship between the reactions and the fixity attention in unconscious of youths who are players Joust . 4. Research's theory There is relation between the reactions and the fixity attention in unconscious of youths who are players Joust 5. Research's spheres - human sphere -timer sphere - place sphere Chapter two It includes some of theoretical & similar studies Chapter three It contents the scientific programs and the practice procedures and the tools or ways which used I the research . Chapter four This has showing the results and their analysis and making discussing or the changing all Chapter five 1. conclusions to improve the theory of the research that there is relation between the reactions and the fixity attention in unconscious of youths who are players Joust 2. Recommended We have fixed some recommended which are used at develop the attention and moving reactions in new researches and similar studies in the future.